If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 9n + -1(-4) Multiply -1 * -4 22 = 9n + 4 Reorder the terms: 22 = 4 + 9n Solving 22 = 4 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. 22 + -9n = 4 + 9n + -9n Combine like terms: 9n + -9n = 0 22 + -9n = 4 + 0 22 + -9n = 4 Add '-22' to each side of the equation. 22 + -22 + -9n = 4 + -22 Combine like terms: 22 + -22 = 0 0 + -9n = 4 + -22 -9n = 4 + -22 Combine like terms: 4 + -22 = -18 -9n = -18 Divide each side by '-9'. n = 2 Simplifying n = 2
| 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 | | 16-7x=-61 | | 10m+9n+4m= | | -4+6(-6+10h)-4h= | | 1.8d+3=2(.9d-1.5) | | A(x)=2x+8x+14 | | 3m+7=7m+6 | | -12+5k=15-45 | | (9x-6)+(3x+8)= | | 7(2+9g)= | | 7.50x+4.75x=891.25 | | 6(3+5y)+(y-8)=13 | | f(x)=-5x+5 | | -10(-2s+1)+6= | | -3x-10=-9x-2 | | log[b](y-3)-log[b](y-4)=log[b](y+3)-log[b]y | | -8a+7(1+5a)=-17+3a | | -5+20x+5x+10=180 | | 5y-1=2y | | -x+3y=28 | | 2x=5x-1 | | 2(3+4(g+1))=-2 | | 10(1+6x)= | | 3m+4m=-63 | | X^2+3=8x+8 | | 3n/2=20 | | -14+12x^2=0 |